Variability of selected extreme meteorological events in Poland - Łupikasza, Ewa; Bielec-Bąkowska, Zuzanna; Falarz, Małgorzata (IGiPZ PAN, 2009)
The principal aim of this paper is to analyze the trends of the multi-annual course of the selected characteristics of extreme precipitation, snow cover and atmospheric thunderstorms in the second half of the twentieth century in Poland. The results of these investigations show that in Poland it is only possible to determine a weak decreasing trend of extreme precipitation events in the S and especially in the SW part of the country. In northern Poland, opposite, although similarly weak, trends have also been observed. It is assumed that the most essential features of long-term changeability of extreme precipitation include a higher than average number of days with extremely high precipitation during the 1960s and 1970s, a distinctly lower frequency of such days during the 1950s, 1980s and in the first half of the1990s. In Poland it is possible to distinguish four broad homogenous areas in terms of the long-term changes in the occurrence of extreme precipitation events. There is considerable regional differentiation when it comes to the occurrence of thunderstorms in Poland, and their long-term changeability does not show any clear trends. Only three stations have determined a weak increase in the number of thunderstorms during the last 120 years. In some stations, an increase in the number of days with thunderstorms during the winter seasons was also observed. There were no significant trends in extreme snow cover in Poland. The periods that contained large and small areas of extreme snow cover thickness occurred alternately. Since the winter season 1987/88, the area of extremely thin snow cover has remained at a relatively high level.
24 cm
Keywords: extreme precipitation; thunderstorm; extreme snow cover; trends; Poland